CONTROL of THE CENTRAL CHEMOREFLEX BY A5 NORADRENERGIC NEURONS IN RATS - Taxini, C. L. [UNESP]; Takakura, A. C.; Gargaglioni, L. H. [UNESP]; Moreira, T. S. (Pergamon-Elsevier B.V. Ltd, 2011)
Central chemoreflex stimulation produces an increase in phrenic nerve activity (PNA) and sympathetic nerve activity (SNA). The A5 noradrenergic region projects to several brainstem areas involved in autonomic regulation and contributes to the increase in SNA elicited by peripheral chemoreflex activation. The aim of the present study was to further test the hypothesis that the A5 noradrenergic region could contribute to central chemoreflex activation. In urethane-anesthetized, sino-aortic denervated, and vagotomized male Wistar rats (n=6-8/group), hypercapnia (end-expiratory CO(2) from 5% to 10%) increased mean arterial pressure (MAP; Delta= +33+/-4 mmHg, P<0.05), splanchnic SNA (sSNA; Delta=+97+/-13%, P<0.05), and PNA frequency and amplitude. Bilateral injection of muscimol (GABA-A agonist; 2 mM) into the A5 noradrenergic region reduced the rise in MAP (Delta=+19+/-3 mmHg, P<0.05), sSNA (Delta= +63+/-5%, P<0.05), and PNA frequency and amplitude produced by hypercapnia. Injections of the immunotoxin anti-dopamine beta-hydroxylasesaporin (anti-D beta H-SAP) into the A5 region destroyed TH(+) neurons but spared facial motoneurons and the chemosensitive neurons in the retrotrapezoid nucleus that express the transcription factor Phox2b and that are non-catecholaminergic (TH(-)Phox2b(+)). Two weeks after selective destruction of the A5 region with the anti-DIM-SAP toxin, the increase in MAP (Delta=+22+/-5 mmHg, P<0.05), sSNA (Delta=+68+/-9%, P<0.05), and PNA amplitude was reduced after central chemoreflex activation. These results suggest that A5 noradrenergic neurons contribute to the increase in MAP, sSNA, and PNA activation during central chemoreflex stimulation. (C) 2011 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: chemoreflex; cardiorespiratory responses; A5 region; sympathetic; phrenic nerve